2011
DOI: 10.1186/1745-6215-12-194
|View full text |Cite
|
Sign up to set email alerts
|

A meta-review of evidence on heart failure disease management programs: the challenges of describing and synthesizing evidence on complex interventions

Abstract: BackgroundDespite favourable results from past meta-analyses, some recent large trials have not found Heart Failure (HF) disease management programs to be beneficial. To explore reasons for this, we evaluated evidence from existing meta-analyses.MethodsSystematic review incorporating meta-review was used. We selected meta-analyses of randomized controlled trials published after 1995 in English that examined the effects of HF disease management programs on key outcomes. Databases searched: MEDLINE, EMBASE, Coch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
61
2
7

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(70 citation statements)
references
References 53 publications
(199 reference statements)
0
61
2
7
Order By: Relevance
“…7 Since the seminal trials of heart failure disease management in the 1990s, 8,9 several meta-analyses have demonstrated the benefits of multidisciplinary approaches in decreasing hospitalizations, improving quality of life, and decreasing mortality. [10][11][12] A metareview of 15 meta-analyses over the past decade found that although most analyses showed a clear benefit, it was difficult to calculate the point estimate of the benefit because of the heterogeneity of the results between trials. 12 In addition, other systematic reviews examined program components, such as transitional care 13 and telehealth.…”
Section: Introductionmentioning
confidence: 98%
“…7 Since the seminal trials of heart failure disease management in the 1990s, 8,9 several meta-analyses have demonstrated the benefits of multidisciplinary approaches in decreasing hospitalizations, improving quality of life, and decreasing mortality. [10][11][12] A metareview of 15 meta-analyses over the past decade found that although most analyses showed a clear benefit, it was difficult to calculate the point estimate of the benefit because of the heterogeneity of the results between trials. 12 In addition, other systematic reviews examined program components, such as transitional care 13 and telehealth.…”
Section: Introductionmentioning
confidence: 98%
“…Depressed patients reacted a little worse on the program, but there were no any statistical significance for the risk of primary endpoints. Программы управления болезнью (ПУБ)/(DMP), представляющие собой обучение пациентов и активный амбулаторный контроль, получили широкое распростра-нение в общей структуре медицинской помощи пациен-там с сердечной недостаточностью (СН) в развитых стра-нах и рекомендованы ведущими профессиональными сообществами [1][2][3][4]. Однако исследования показывают, что эффективность таких программ может широко варь-ировать в зависимости от их структуры и содержания, а также в зависимости от базовых характеристик вклю-ченных пациентов.…”
Section: Influence Of Psychoemotional Disorders On the Effectiveness unclassified
“…Improved self-management has been associated with reduced mortality, hospital admissions, and healthcare costs [5,6]. For example, a trial of nurse-led education to improve selfmanagement in heart failure demonstrated significant reductions in cardiac (20%) and heart failure-related (17%) [6] hospitalisations.…”
Section: Introductionmentioning
confidence: 99%